Modelling Event-Based Interactions in Component-Based Architectures for Quantitative System Evaluation - Rathfelder, Christoph (The Karlsruhe Series on Software Design and Quality / Ed. by Prof. Dr. Ralf Reussner, 2013)
This dissertation thesis presents an approach enabling the modelling and quality-of-service prediction of event-based systems at the architecture-level. Applying a two-step model refinement transformation, the approach integrates platform-specific performance influences of the underlying middleware while enabling the use of different existing analytical and simulation-based prediction techniques.